SGLT2 Inhibitors in Patients with Chronic Kidney Disease and Heart Disease: A Literature Review - Abhishek Kansara; Faiza Mubeen; Jawairia Shakil (Methodist DeBakey Cardiovascular Journal)
Sodium-glucose transport protein 2 inhibitors, commonly referred to as SGLT2i, are a group of prescription pharmaceuticals that are approved by the United States Food and Drug Administration for use with diet and exercise to lower blood glucose in adults with type 2 diabetes. Diabetes is a well-recognized major contributor to cardiovascular and renal disease burden. In addition to blood glucose control, SGLT2i have been shown to provide significant cardiovascular and renoprotective benefits in patients with and without diabetes. In this review, we describe current evidence related to the renal and cardiovascular benefits of using SGLT2i.